Pengaruh Pengalaman Magang, Motivasi Kerja, dan Soft Skill Terhadap Kesiapan Kerja Mahasiswa Dalam Memasuki Dunia Kerja - Ariestya Putri Pambajeng; Sumartik Sumartik; Herlinda Maya Kumala (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to identify the impact of internship experience, work motivation, and soft skills on student readiness to enter the world of work. The population in this study were students in the Management Study Program, Faculty of Business, Law and Social Sciences, Muhammadiyah University of Sidoarjo class of 2019. The quantitative research method and sample used were 110 students who were selected through non-probability sampling with a systematic sampling method. Data was collected through the use of a questionnaire with a Likert scale as a measurement scale. By using multiple linear regression analysis techniques in data analysis with the SPSS 25 analysis tool. The results of the study have fulfilled good validity so that the model is declared feasible. Based on data analysis, it can be concluded that there is a positive and significant influence partially or simultaneously between internship experience, work motivation, and soft skills on student work readiness in entering the world of work. Keywords: Internship Experience; Work Motivation; Soft Skills; Working readiness.